Optical laminate and image display device using the same
By using an adhesive layer with high hardness and high elastic modulus in the optical laminate, deformation of the liquid crystal orientation fixing layer is suppressed, and the problems of low productivity and reduced anti-reflection function of the optical laminate in the prior art are solved, thereby achieving an efficient manufacturing process and good optical performance.
Patent Information
- Application Number
- CN202411391365.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-06
- Filing Date
- 2024-10-08
- Publication Date
- 2025-04-08
AI Technical Summary
The existing optical laminates are prone to deform during the transfer of the liquid crystal film, resulting in a decrease in anti-reflection function and a decrease in productivity.
Using a polarizer including a polarizer and an optical laminated body design with a liquid crystal oriented fixing layer laminated by an adhesive layer, the adhesive layer has a high hardness, elastic modulus and indentation load to suppress deformation of the liquid crystal oriented fixing layer.
The deformation of the liquid crystal oriented fixing layer during the transfer process is effectively suppressed, the productivity of the optical laminate is improved, and the good anti-reflection function is maintained.
Smart Images

Figure CN119781108A_ABST
Abstract
Description
Technical Field The present invention relates to an optical laminate and an image display device using the optical laminate. Background Art In recent years, image display devices typified by liquid crystal display devices and electroluminescent (EL) display devices (e.g., organic EL display devices or inorganic EL display devices) have rapidly gained wider use. In image display devices, an optical laminate (e.g., JP 2014-222282A) including a retardation film (e.g., an antireflection film obtained by integrating a polarizer and a retardation film) is used in many cases. In recent years, with the increasing demand for thinning of image display devices, the demand for thinning of optical laminates has also increased. Considering the thinning of the optical laminate, the thinning of a retardation layer (retardation film) that contributes greatly to the thickness is in progress. A typical example of a thin retardation film is a film obtained by aligning and fixing the alignment state of a liquid crystal compound (hereinafter referred to as "liquid crystal film"). Since the liquid crystal compound has a very large birefringence (Δn) compared with a resin, the thickness of the liquid crystal film that can be used to obtain a desired in-plane retardation can be made very thin compared with a stretched film of a resin film. In the production of an optical laminate (typically, the above antireflection film), the liquid crystal film is typically transferred onto a polarizer. However, when transferring such a liquid crystal film, the liquid crystal film is deformed, and the antireflection function of the deformed portion becomes insufficient and is sometimes lost. As a result, the productivity (yield) of the optical laminate may become insufficient. Summary of the Invention The present invention has been made to solve the problems of the above prior art, and its main object is to provide an optical laminate having a liquid crystal alignment fixing layer that suppresses deformation of the liquid crystal alignment fixing layer during transfer during manufacturing and can be manufactured with high productivity.
[0001] According to at least one embodiment of the present invention, there is provided an optical laminate. The optical laminate includes: a polarizer including a polarizer; and a retardation layer laminated on the polarizer via an adhesive layer, wherein the retardation layer includes a first liquid crystal alignment fixing layer and a second liquid crystal alignment fixing layer in this order from the polarizer side, wherein the retardation layer as a whole has one of a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650), and wherein the adhesive layer has a hardness of 50 MPa or more, an elastic modulus of 800 MPa or more, and an indentation load of 900 μN or more.
[0002] In the above item [1], the adhesive layer contains an active energy ray curable adhesive.
[0003] In the above item [2], the active energy ray curable adhesive contains acrylmorpholine as a curing component.
[0004] In the above item [3], the active energy ray-curable adhesive further contains tripropylene glycol diacrylate, phenoxydiethylene glycol acrylate and 3-methacrylamidephenylboric acid as curing components.
[0005] In any one of the above items [1] to [4], the adhesive layer has a hardness of 70 MPa or more, an elastic modulus of 1,500 MPa or more, and an indentation load of 1,300 μN or more.
[0006] In any one of the above items [1] to [5], the thickness of the first liquid crystal alignment fixing layer is 1.7 μm or less.
[0007] According to another aspect of the present invention, there is provided an image display device comprising the optical layered body according to any one of the above items [1] to [6]. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 is a schematic cross-sectional view of an optical stack according to at least one embodiment of the present invention. DETAILED DESCRIPTION Hereinafter, representative embodiments of the present invention will be described, but the present invention is not limited to these embodiments. (Definition of terms and symbols) Definitions of terms and symbols used herein are as follows. (1) Refractive index (nx, ny and nz) “nx” represents the refractive index in the direction of maximum refractive index in the plane (ie, slow axis direction), “ny” represents the refractive index in the direction perpendicular to the slow axis in the plane (ie, fast axis direction), and “nz” represents the refractive index in the thickness direction. (2) In-plane retardation (Re) "Re(λ)" refers to the in-plane retardation of a film measured with light having a wavelength of λ nm at 23° C. For example, "Re(550)" refers to the in-plane retardation of a film measured with light having a wavelength of 550 nm at 23° C. Re(λ) is determined by the equation "Re=(nx-ny)×d" when the thickness of the film is expressed as "d" (nm). (3) Thickness direction retardation (Rth) "Rth(λ)" refers to the retardation in the thickness direction of the film measured at 23°C with light having a wavelength of λnm. For example, "Rth(550)" refers to the retardation in the thickness direction of the film measured at 23°C with light having a wavelength of 550nm. Rth(λ) is determined by the equation "Rth = (nx-nz) × d" when the thickness of the film is expressed as "d" (nm). (4) Nz coefficient The Nz coefficient is determined by the equation "Nz = Rth / Re". (5) Angle When referring to an angle herein, unless otherwise specified, the angle encompasses angles in both the clockwise and counterclockwise directions. A. Optical laminate Figure 1 1 is a schematic cross-sectional view of an optical laminate according to at least one embodiment of the present invention. The optical laminate 100 of the illustrated example is provided with a polarizer 10 and a retardation layer 20. The polarizer 10 and the retardation layer 20 are stacked via an adhesive layer 30. The polarizer 10 is typically provided with a polarizer 11, and protective layers 12 and 13 arranged on both sides of the polarizer 11. At least one of the protective layers 12 or 13 may be omitted depending on the purpose. Therefore, the polarizer may be a so-called double-sided protective polarizer or a so-called single-sided protective polarizer, or may be formed by a polarizer alone. The delay layer 20 includes a first liquid crystal orientation fixing layer 21 and a second liquid crystal orientation fixing layer 22 in sequence from the polarizer 10 side. The first liquid crystal orientation fixing layer 21 and the second liquid crystal orientation fixing layer 22 are stacked via any appropriate adhesive layer (not shown: sometimes referred to as "interlayer adhesive layer" below). When a liquid crystal orientation fixing layer is used as a delay layer, the desired in-plane delay can be achieved with a thickness much smaller than that of a stretched film of a resin film. Thus, a significant thinning of the optical laminate can be achieved. The delay layer 20 as a whole (as a stack of the first liquid crystal orientation fixing layer 21 and the second liquid crystal orientation fixing layer 22) has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650). In at least one embodiment of the present invention, the Nz coefficient of the delay layer as a whole can be, for example, 0.30 to 0.70. As used herein, the term "liquid crystal orientation fixing layer" refers to the following layer: a liquid crystal compound is oriented in a predetermined direction in the layer, and its orientation state is fixed. The term "liquid crystal orientation fixing layer" is a concept including an orientation solidification layer obtained by solidifying liquid crystal monomers. In at least one embodiment of the present invention, the adhesive layer 30 has a hardness of 50MPa or more, an elastic modulus of 800MPa or more, and an indentation load of 900μN or more. When the adhesive layer has such a configuration, it is possible to suppress the deformation when the delay layer (substantially the first liquid crystal orientation fixing layer) is transferred to the polarizer via the adhesive layer during the manufacture of the optical laminate. Therefore, the reduction of the anti-reflection function caused by deformation is suppressed (the loss in the worst case: the reduction and loss of the anti-reflection function are sometimes collectively referred to as "reduction of anti-reflection function, etc." below). As a result, the yield is improved, and the optical laminate can be obtained with a significantly high productivity. When the inventors of the present invention studied the further thinning of the optical laminate having a liquid crystal orientation fixing layer as a delay layer, they encountered the following problem: if the liquid crystal orientation fixing layer is further thinned, a portion of the anti-reflection function, etc., is formed in the obtained optical laminate, and the yield is reduced. The inventors of the present invention have conducted extensive research on this local reduction of the anti-reflection function, etc., and found that deformations such as sagging after the adhesive layer and the delay layer are stretched, which have not been observed so far, occur, and this deformation leads to a reduction in the anti-reflection function, etc. Furthermore, the inventors of the present invention have found that such deformation can be suppressed by optimizing a plurality of characteristics regarding the hardness of the adhesive layer, thereby completing the present invention. The hardness (indentation hardness) of the adhesive layer is preferably 55 MPa or greater, more preferably 60 MPa or greater, further preferably 65 MPa or greater, particularly preferably 70 MPa or greater, especially preferably 85 MPa or greater, and most preferably 100 MPa or greater. The hardness of the adhesive layer may be, for example, 180 MPa or less, or, for example, 150 MPa or less. The elastic modulus (indentation elastic modulus) of the adhesive layer is preferably 900 MPa or greater, more preferably 1,000 MPa or greater, still more preferably 1,200 MPa or greater, particularly preferably 1,400 MPa or greater, particularly preferably 1,600 MPa or greater, and most preferably 1,900 MPa or greater. The elastic modulus of the adhesive layer may be, for example, 2,700 MPa or less, and may also be, for example, 2,400 MPa or less. The indentation load of the adhesive layer is preferably 1,000 μN or greater, more preferably 1,200 μN or greater, more preferably 1,300 μN or greater, particularly preferably 1,400 μN or greater, especially preferably 1,800 μN or greater, and most preferably 2,200 μN or greater. The indentation load of the adhesive layer may be, for example, 3,000 μN or less, and, for example, may also be 2,800 μN or less. The hardness and elastic modulus can generally be measured by a nanoindentation method using an indentation tester (generally a nanoindenter). More specifically, the hardness is calculated by the maximum load Pmax and the contact projection area A between the indenter and the object to be measured by the formula shown below, and the maximum load Pmax is obtained by a displacement-load hysteresis curve obtained by pressing the probe (indenter) into the surface of the object to be measured. Hardness (GPa) = Pmax / A The elastic modulus is calculated by the following formula from the contact projection area A, the slope of the tangent line of the unloading curve of the displacement-load hysteresis curve (contact stiffness) S, and √π. Elastic modulus (GPa) = (√π / 2) × (S / √A) The indentation load is the load required to push the measured object by 1,000 nm. Any suitable configuration can be adopted for the adhesive layer 30, as long as the above-mentioned characteristics are met. Specifically, the adhesive layer can include an adhesive or a pressure-sensitive adhesive. That is, the adhesive layer can be an adhesive layer or a pressure-sensitive adhesive layer. The adhesive layer generally includes an adhesive that can be cured by active energy rays (generally electron beams, UV light or visible light). By such a configuration, an adhesive layer that satisfies the above-mentioned desired characteristics can be easily formed. In addition, by such a configuration, the adhesive layer can be thinned, and a very thin optical laminate can be obtained. In the optical laminate, the total thickness from the first liquid crystal orientation fixing layer to the second liquid crystal orientation fixing layer is preferably 20 μm or less, more preferably 3 μm to 10 μm. According to at least one embodiment of the present invention, when manufacturing an optical laminate having an extremely thin liquid crystal orientation fixing layer, the deformation of the liquid crystal orientation fixing layer during transfer can be suppressed, so that the optical laminate can be obtained with high productivity. When the total thickness from the first liquid crystal orientation fixing layer to the second liquid crystal orientation fixing layer falls within the above range, the total thickness from the polarizer to the second liquid crystal orientation fixing layer (the actual total thickness of the optical laminate, excluding the thickness of the pressure-sensitive adhesive used to bond to the image display panel) can be, for example, 100 μm or less, and can also be, for example, 30 μm to 80 μm. In order to be able to be bonded to the image display panel when the optical laminate is actually used, the outermost layer on the second liquid crystal orientation fixing layer side (image display panel side) includes a pressure-sensitive adhesive layer (not shown). In this case, it is preferred to temporarily bond a release liner to the surface of the pressure-sensitive adhesive layer until the optical laminate is used. When the release liner is temporarily bonded, the pressure-sensitive adhesive layer can be protected and the optical laminate can be formed into a roll. Hereinafter, the components of the optical layered body will be described in detail. B. Polarizer B-1. Polarizer The polarizer 11 typically includes a polyvinyl alcohol (PVA)-based resin film containing a dichroic substance such as iodine. Examples of PVA-based resins include polyvinyl alcohol, partially formalized polyvinyl alcohol, ethylene-vinyl alcohol copolymer, ethylene-vinyl acetate copolymer-based partially saponified products, and the like. The PVA-based resin preferably contains acetoacetyl-modified PVA-based resin. By such configuration, a polarizer with desired mechanical strength can be obtained. When the total amount of the PVA-based resin is set to 100wt%, the blending amount of the acetoacetyl-modified PVA-based resin is preferably 5wt% to 20wt%, more preferably 8wt% to 12wt%. When the blending amount falls within such a range, a polarizer with more excellent mechanical strength can be obtained. The polarizer preferably contains iodide or sodium chloride (sometimes collectively referred to as "halide"). Examples of iodides include potassium iodide, sodium iodide and lithium iodide. The content of halide in the polarizer is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, relative to 100 parts by weight of PVA-based resin. The halide is blended into a coating solution for forming a PVA-based resin layer as a precursor of the polarizer in the manufacturing method described later, and can be ultimately introduced into the polarizer. When the halide is introduced into the polarizer, the orientation properties of the PVA molecules in the polarizer can be improved, and thus a polarizer with excellent optical properties (typically, high polarization degree and high single-layer transmittance) can be achieved. The polarizer preferably exhibits absorption dichroism at any wavelength within the wavelength range of 380nm to 780nm. The monolayer transmittance of the polarizer is preferably 41.0% to 46.0%, more preferably 42.0% to 45.0%. The polarization degree of the polarizer is preferably 97.0% or greater, more preferably 99.0% or greater, and further preferably 99.9% or greater. According to at least one embodiment of the present invention, even when the monolayer transmittance falls within the above range, the polarization degree can be maintained within such a range. The thickness of the polarizer is, for example, 25 μm or less. In at least one embodiment of the present invention, the thickness of the polarizer can be, for example, 12 μm to 22 μm, and can also be, for example, 15 μm to 20 μm. A polarizer with such a thickness can generally be obtained by dyeing a PVA base film with iodine and uniaxially stretching the PVA base film. In at least one embodiment of the present invention, the thickness of the polarizer can be, for example, 10 μm or less, and can also be, for example, 1 μm to 8 μm, and can also be, for example, 3 μm to 7 μm. A polarizer with such a thickness can generally be obtained by stretching and dyeing a laminate of a resin substrate and a PVA-based resin layer formed on the resin substrate by coating to form the PVA-based resin layer into a polarizer. The polarizer can be produced by any appropriate method. For example, the resin film used to form the polarizer may be a single-layer resin film or a laminate of two or more layers. Specific examples of the polarizer comprising a monolayer resin film include: hydrophilic polymer films, such as PVA base films, partially formalized PVA base films, and ethylene-vinyl acetate copolymer-based partially saponified films, which have been dyed and stretched with a dichroic substance such as iodine or a dichroic dye; and polyene-based oriented films, such as a dehydrated product of PVA and a dehydrochlorinated product of polyvinyl chloride. It is preferred to use a polarizer obtained by iodine dyeing and uniaxial stretching of the PVA base film because the optical properties of such a polarizer are excellent. Dyeing with iodine is carried out, for example, by immersing the PVA base film in an aqueous solution of iodine. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. Stretching can be carried out after the dyeing process, or can be carried out while dyeing. In addition, dyeing can be carried out after stretching. As required, the PVA base film is subjected to swelling treatment, cross-linking treatment, washing treatment, drying treatment, etc. For example, when washing with water by immersing the PVA base film in water before dyeing, pollutants and anti-blocking agents on the surface of the PVA base film can be washed off, and in addition, the PVA base film can be swollen to prevent uneven dyeing, etc. As a specific example of a polarizer obtained using the above-mentioned laminate, there is a polarizer obtained using the following substances: a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate; or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The polarizer obtained by using a laminate of a resin substrate and a PVA-based resin layer formed on the resin substrate by coating can be manufactured, for example, by: applying a PVA-based resin solution to the resin substrate; drying the solution to form a PVA-based resin layer on the resin substrate, thereby providing a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to convert the PVA-based resin layer into a polarizer. In at least one embodiment of the present invention, it is preferred that a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on a single side of the above-mentioned resin substrate. Stretching typically includes stretching the laminate while the laminate is immersed in an aqueous boric acid solution. In addition, as required, before stretching in the boric acid aqueous solution, the stretching may also include stretching the laminate in the air at a high temperature (e.g., 95°C or higher). In addition, in at least one embodiment of the present invention, it is preferred to subject the laminate to a drying shrinkage treatment, which includes heating the laminate while conveying the laminate in its length direction so that the laminate shrinks by 2% or more in its width direction. The manufacturing method of at least one embodiment of the present invention typically includes sequentially subjecting the laminate to an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment. When auxiliary stretching is introduced, the crystallinity of PVA can be improved even when PVA is applied to a thermoplastic resin, so that high optical properties can be achieved. In addition, if the orientation of PVA is increased in advance while improving the crystallinity, then in the subsequent dyeing process or stretching process, when the laminate is immersed in water, problems such as reduction in orientation and dissolution of PVA can be prevented, and high optical properties can be achieved. In addition, when the PVA-based resin layer is immersed in a liquid, the orientation disorder of the polyvinyl alcohol molecules and the reduction of their orientation can be suppressed compared to the case where the PVA-based resin layer does not contain any halide. Therefore, the optical properties of the polarizer obtained by the treatment steps (such as dyeing treatment and underwater stretching treatment) carried out by immersing the laminate in a liquid can be improved. In addition, the optical properties can be improved by shrinking the laminate in its width direction through a drying shrinkage treatment. The laminate of the resulting resin substrate and the polarizer can be used directly (that is, the resin substrate can be used as a protective layer of the polarizer), or any appropriate protective layer can be stacked on the peeling surface of the resin substrate or on the surface opposite to the peeling surface from the laminate of the resin substrate and the polarizer according to the purpose. The details of the manufacturing method of such a polarizer are recorded in, for example, Japanese Patent Application Publication No. 2012-73580 and Japanese Patent No. 6470455, and the entire contents of these records are incorporated into this specification by reference. B-2. Protective layer The protective layers 12 and 13 each include any appropriate resin film. As the forming material of the resin film, representative examples include cellulose-based resins such as triacetyl cellulose (TAC), cycloolefin-based resins such as polynorbornene, (meth) acrylic resins, polyester-based resins such as polyethylene terephthalate (PET) or polyethylene naphthalate (PEN), polyolefin-based resins such as polyethylene, polycarbonate-based resins, etc. A representative example of (meth) acrylic resin is a (meth) acrylic resin with a lactone ring structure. The (meth) acrylic resin with a lactone ring structure is described in, for example, Japanese Patent Application Publication No. 2000-230016, Japanese Patent Application Publication No. 2001-151814, Japanese Patent Application Publication No. 2002-120326, Japanese Patent Application Publication No. 2002-254544 and Japanese Patent Application Publication No. 2005-146084, which are incorporated herein by reference. Among them, from the viewpoint of ease of processing into irregular shapes, for example, cellulose-based resins are preferred, and TAC is more preferred. From the viewpoint of low moisture permeability and the ability to obtain a polarizing plate with excellent durability, cycloolefin-based resins and (meth) acrylic resins are preferred. In at least one embodiment of the present invention, the protective layer 12 may include TAC, and the protective layer 13 may include a (meth) acrylic resin. The optical stack is typically configured on the observer side of the image display device, and the protective layer 12 is typically arranged on its observer side. Therefore, the protective layer 12 can be surface-treated as needed. Examples of surface treatments include hard coating treatments, anti-reflection treatments, anti-sticking treatments, and anti-glare treatments. In addition / optionally, the protective layer 12 can be treated as needed to improve visibility when viewed through polarized sunglasses (typically imparting circular (elliptical) polarization functions or imparting ultra-high delay). When such a treatment is performed, even when viewing the display screen through a polarized lens as in polarized sunglasses, excellent viewing can be achieved. Therefore, the optical stack can even be suitably applied to image display devices that can be used outdoors. In at least one embodiment of the present invention, the protective layer 13 is preferably optically isotropic. The phrase "optically isotropic" as used herein means that the layer has an in-plane retardation Re(550) of 0nm to 10nm and a thickness direction retardation Rth(550) of -10nm to +10nm. The thickness of each of the protective layers 12 and 13 is preferably 10 to 80 μm, more preferably 12 to 40 μm, and even more preferably 15 to 35 μm. When the protective layer 12 is surface treated, the thickness of the protective layer 12 includes the thickness of the surface treated layer. C. Delay layer As described above, the retardation layer 20 includes a first liquid crystal alignment fixing layer 21 and a second liquid crystal alignment fixing layer 22 in this order from the polarizer side. Further, as described above, the retardation layer 20 as a whole (as a laminate of the first liquid crystal alignment fixing layer 21 and the second liquid crystal alignment fixing layer 22) has a circular polarization function or an elliptical polarization function, and has the relationship of Re(450) < Re(550) < Re(650). Regarding the description of the retardation layer in this part, when the retardation layer is simply referred to as the "retardation layer", the retardation layer means the description of the whole retardation layer, and when the retardation layer is simply referred to as the "liquid crystal alignment fixing layer", the retardation layer means the common description of the first liquid crystal alignment fixing layer and the second liquid crystal alignment fixing layer. The Re(550) of the retardation layer 20 is preferably from 100 nm to 200 nm, more preferably from 110 nm to 180 nm, still more preferably from 120 nm to 170 nm, and particularly preferably from 130 nm to 150 nm. When the Re(550) of the retardation layer falls within such a range, the retardation layer can exhibit a satisfactory circular polarization function or elliptical polarization function in combination with a polarizer. The retardation layer 20 has the relationship of Re(450) < Re(550) < Re(650). That is, the retardation layer 20 preferably exhibits an inverse wavelength dispersion dependence in which its retardation value increases as the wavelength of the measurement light increases. With such a configuration, a satisfactory antireflection function can be achieved in a very wide wavelength band. Re(450) / Re(550) is, for example, greater than 0.5 and less than 1.0, preferably from 0.7 to 0.95, more preferably from 0.75 to 0.92, and still more preferably from 0.8 to 0.9. The ratio "Re(650) / Re(550)" is preferably 1.0 or greater and less than 1.15, more preferably from 1.03 to 1.1. In at least one embodiment of the present invention, as described above, the retardation layer 20 may have an Nz coefficient of, for example, 0.30 to 0.70. Therefore, the retardation layer 20 exhibits a refractive index characteristic of nx > nz > ny. According to such a structure, reflection in the tilt direction can be well prevented, and an antireflection function can be exhibited within a wide viewing angle range. The Nz coefficient is preferably from 0.35 to 0.65, more preferably from 0.40 to 0.60, and still more preferably from 0.45 to 0.55. As the liquid crystal compound used in the liquid crystal orientation fixing layer, liquid crystal polymers and liquid crystal monomers can be cited. The liquid crystal compound is preferably polymerizable (i.e., a liquid crystal monomer). In the case where the liquid crystal compound is polymerizable, the orientation state of the molecules of the liquid crystal compound can be fixed by orienting the molecules of the liquid crystal compound and then polymerizing the compound. In this case, the polymer formed by polymerization is non-liquid crystal. Therefore, the formed liquid crystal orientation fixing layer will not experience a transition caused by temperature changes, such as to a liquid crystal phase, a glass phase, or a crystalline phase, which is unique to liquid crystal compounds. As a result, the liquid crystal orientation fixing layer becomes a delay layer with extremely excellent stability that is not affected by temperature changes. In at least one embodiment of the present invention, the liquid crystal orientation fixing layer can be formed using a composition containing a polymerizable liquid crystal compound (polymerizable liquid crystal compound, i.e., liquid crystal monomer). In this specification, the "polymerizable liquid crystal compound" in the composition refers to a compound having a polymerizable group and having liquid crystal properties. A polymerizable group refers to a group that participates in a polymerization reaction, preferably a photopolymerizable group. In this specification, a "photopolymerizable group" refers to a group that can participate in a polymerization reaction via an active free radical or acid generated, for example, by a photopolymerization initiator. For example, polymerizable mesogen compounds described in Japanese Patent Translation Publication No. 2002-533742 (WO 00 / 37585A1), European Patent No. 358208 (U.S. Patent No. 5211877), European Patent No. 66137 (U.S. Patent No. 4388453), WO 93 / 22397A1, European Patent Application Publication No. 0261712, German Patent Application Publication No. 19504224, German Patent Application Publication No. 4408171, British Patent No. 2280445, etc., etc. can each be used as a liquid crystal monomer. Specific examples of such polymerizable mesogen compounds include products available from BASF SE under the product name "LC242", products available from Merck KGaA under the product name "E7", and products available from Wacker Chemie AG under the product name "LC-Silicon-CC3767". The liquid crystal compound may be thermotropic or lyotropic in its liquid crystal properties. In addition, the configuration of the liquid crystal phase may be nematic liquid crystal or smectic liquid crystal. From the viewpoint of ease of manufacture, nematic liquid crystal having thermotropic liquid crystal properties is preferred. The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on its type. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C. The birefringence Δn of the liquid crystal orientation fixing layer is preferably 0.06 or greater, more preferably 0.08 or greater, further preferably 0.09 or greater, and particularly preferably 0.10 or greater. The upper limit of Δn may be, for example, 0.13, or may be, for example, 0.12. When Δn falls within such a range, the desired in-plane delay can be achieved with a very small thickness. Thus, the thickness of each of the liquid crystal orientation fixing layer and the optical laminate can be further reduced, which can ultimately contribute to the significant thinning of the image display device. The liquid crystal alignment fixed layer may exhibit a reverse wavelength dispersion characteristic in which the retardation value increases with an increase in the wavelength of the measuring light, a forward wavelength dispersion characteristic in which the retardation value decreases with an increase in the wavelength of the measuring light, or a flat wavelength dispersion characteristic in which the retardation value remains substantially unchanged even when the wavelength of the measuring light changes. The first liquid crystal orientation fixing layer 21 can typically play the role of a λ / 2 plate, and the second liquid crystal orientation fixing layer 22 can typically play the role of a λ / 4 plate. Specifically, the Re(550) of the first liquid crystal orientation fixing layer is preferably 150nm to 300nm, more preferably 200nm to 270nm, and more preferably 220nm to 260nm, and the Re(550) of the second liquid crystal orientation fixing layer is preferably 100nm to 200nm, more preferably 110nm to 160nm, and more preferably 120nm to 140nm. The thickness of the first liquid crystal orientation fixing layer can be adjusted so that the desired in-plane retardation of the λ / 2 plate can be obtained. In at least one embodiment of the present invention, the thickness of the first liquid crystal orientation fixing layer can be, for example, 2.0μm to 4.0μm. In at least one embodiment of the present invention, the thickness of the first liquid crystal orientation fixing layer is preferably 1.7μm or less, more preferably 1.6μm or less, and further preferably 1.5μm or less. In this case, the thickness of the above-mentioned first liquid crystal orientation fixing layer can be, for example, 1.3μm or more. As described above, according to at least one embodiment of the present invention, while making the thickness of the first liquid crystal orientation fixing layer thinner than that of the prior art, the deformation of the first liquid crystal orientation fixing layer when the first liquid crystal orientation fixing layer is transferred to the polarizer during manufacturing can be suppressed, and as a result, the optical laminate can be manufactured with high productivity. The thickness of the second liquid crystal orientation fixing layer can be adjusted so that the desired in-plane delay of the λ / 4 plate can be obtained. Specifically, the thickness of the layer can be, for example, 0.8μm to 2.5μm. The angle between the slow axis of the first liquid crystal orientation fixing layer and the transmission axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably 14° to 16°, and the angle between the slow axis of the second liquid crystal orientation fixing layer and the transmission axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and further preferably 74° to 76°. The arrangement order of the first liquid crystal alignment fixed layer and the second liquid crystal alignment fixed layer can be reversed, and the angle formed by the slow axis of the first liquid crystal alignment fixed layer and the transmission axis of the polarizer, and the angle formed by the slow axis of the second liquid crystal alignment fixed layer and the transmission axis of the polarizer can be reversed. The refractive index of the liquid crystal alignment fixing layer may vary depending on the composition used to form the liquid crystal alignment fixing layer (substantially, the type of liquid crystal compound, the type, amount, combination, blending amount, etc. of additives). LC1 and the refractive index n of the second liquid crystal alignment fixing layer LC2 can be the same or different from each other (the refractive index n of the first liquid crystal alignment fixing layer LC1 It can be larger, or the refractive index n of the second liquid crystal alignment fixing layer LC2 The refractive index n of the first liquid crystal alignment fixing layer may be larger. LC1It is preferably 1.55 to 1.75, and more preferably 1.60 to 1.70. The refractive index n of the second liquid crystal alignment fixing layer LC2 It is preferably 1.45 to 1.65, and more preferably 1.50 to 1.60. The refractive index n of the first liquid crystal alignment fixing layer LC1 and the refractive index n of the second liquid crystal alignment fixing layer LC2 The refractive index n of the first liquid crystal alignment fixing layer is LC1 The refractive index n of the second liquid crystal alignment fixing layer LC2 The absolute value of the difference between may be, for example, 0.00 to 0.20. The liquid crystal orientation fixing layer can typically be formed by applying a composition (liquid crystal composition) for forming a liquid crystal orientation fixing layer to any appropriate substrate and fixing or curing the coated film. The formed liquid crystal orientation fixing layer can be transferred to a predetermined position of the optical laminate via an adhesive layer. More details are described below. In at least one embodiment of the present invention, the first liquid crystal orientation fixing layer is formed by: applying a liquid crystal composition to any appropriate substrate; orienting the liquid crystal compound at a temperature at which the liquid crystal compound exhibits liquid crystallinity; and fixing or curing the applied film in the state where the liquid crystal compound is oriented. The formed first liquid crystal orientation fixing layer is transferred to a polarizer via an adhesive layer. According to at least one embodiment of the present invention, the deformation of the first liquid crystal orientation fixing layer during its transfer can be suppressed. Then, the second liquid crystal orientation fixing layer formed on the substrate in the same manner as above is transferred to the first liquid crystal orientation fixing layer via an interlayer adhesive layer. By suppressing the deformation of the first liquid crystal orientation fixing layer during transfer, the deformation of the second liquid crystal orientation fixing layer during transfer can also be suppressed. Therefore, a delay layer can be formed. A side chain type thermotropic liquid crystal polymer can be introduced into the first liquid crystal orientation fixing layer and / or the second liquid crystal orientation fixing layer (in essence, the liquid crystal composition used to form these layers). If a side chain type thermotropic liquid crystal polymer is introduced, it sometimes produces a homeotropic orientation (vertical orientation) effect on the liquid crystal monomer. As a result, the nz of the first liquid crystal orientation fixing layer and / or the second liquid crystal orientation fixing layer can be made larger, and as a result, the Nz coefficient of the first liquid crystal orientation fixing layer and / or the second liquid crystal orientation fixing layer can be set to fall within the above-mentioned desired range. Finally, even if the positive C plate described later is not configured, the Nz coefficient of the delay layer can be set to the above-mentioned desired range. As the side chain type thermotropic liquid crystal polymer, a copolymer having a monomer unit including a thermotropic liquid crystal segment side chain and a monomer unit including a non-liquid crystal segment side chain is generally used. When the side chain type liquid crystal polymer has a thermotropic liquid crystal segment in its side chain, the polymer can be oriented when the liquid crystal composition is heated to a predetermined temperature. In addition, when the side chain type liquid crystal polymer has a non-liquid crystal segment in its side chain, the non-liquid crystal segment interacts with the photopolymerizable liquid crystal monomer, and thus a homeotropic orientation effect on the photopolymerizable liquid crystal monomer may occur. As the side chain type thermotropic liquid crystal polymer, a copolymer containing a liquid crystal monomer unit represented by the general formula (I) and a non-liquid crystal monomer unit represented by the general formula (II) is preferably used. In formula (I), R 1 represents a hydrogen atom or a methyl group, R 2 represents a cyano group, a fluoro group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms, and X 1 "a" represents an integer of 1 to 6, and "b" and "c" each independently represent 1 or 2. In formula (II), R 3 represents a hydrogen atom or a methyl group, R 4 It represents an alkyl group having 7 to 22 carbon atoms, a fluoroalkyl group having 1 to 22 carbon atoms, or a group represented by the following general formula (III). In formula (III), R 5 represents an alkyl group having 1 to 5 carbon atoms, and "d" represents an integer of 1 to 6. The ratio of the liquid crystal monomer unit to the non-liquid crystal monomer unit in the side chain liquid crystal polymer can be appropriately set according to the purpose. The ratio (molar ratio) of the non-liquid crystal monomer to the total of the liquid crystal monomer unit and the non-liquid crystal monomer unit is preferably 0.05 to 0.8, more preferably 0.1 to 0.6, and further preferably 0.15 to 0.5. With this configuration, a liquid crystal orientation fixing layer showing a desired refractive index characteristic (Nz coefficient) can be obtained. The ratio of the liquid crystal monomer in the liquid crystal composition to the side chain type liquid crystal polymer can be appropriately set according to the purpose. When the content of the side chain type liquid crystal polymer is large, there is a tendency that the Nz coefficient decreases, and when the content of the liquid crystal monomer is large, there is a tendency that the Nz coefficient increases. Relative to the content of the side chain type liquid crystal polymer, the content of the liquid crystal monomer is preferably 1.2 times to 20 times, more preferably 1.3 times to 10 times, further preferably 1.4 times to 9 times, and particularly preferably 1.5 times to 8 times. Utilizing this configuration, it is possible to obtain a liquid crystal orientation fixing layer showing a desired refractive index characteristic (Nz coefficient). Details on the side chain type liquid crystal polymer and a method of forming a liquid crystal alignment fixing layer having an Nz coefficient of less than 1.0 are described in Japanese Patent No. 6769921, the description of which is incorporated herein by reference. The retardation layer 20 may further include a positive C plate. The positive C plate has a refractive index characteristic showing the relationship nz>nx=ny. The thickness direction retardation Rth(550) of the positive C plate is preferably -20nm to -300nm, more preferably -30nm to -250nm, further preferably -40nm to -200nm, and particularly preferably -50nm to -150nm. Here, "nx=ny" includes not only the case where nx and ny are completely equal to each other, but also the case where nx and ny are approximately equal. That is, the in-plane retardation Re(550) of the positive C plate can be less than 10nm. The positive C plate can be formed, for example, using a composition containing the above-mentioned side chain type liquid crystal polymer. As a method for forming the positive C plate, specifically, for example, the method described in
[0020] to
[0028] of Japanese Patent Application Publication No. 2002-333642 can be cited. At this time, the thickness of the positive C plate is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and further preferably 0.5 μm to 5 μm. D. Adhesive layer Any appropriate configuration may be adopted for the adhesive layer 30 as long as the above-described desired characteristics are achieved. The adhesive layer 30 may typically include an active energy ray-curable adhesive as described above. Active energy ray curing adhesives typically include a curing component and a photopolymerization initiator. The curing component is typically a compound that can be free radical polymerized. Examples of curing components include higher alkyl esters of (meth) acrylic acid and modified products thereof. Specific examples thereof include ε-caprolactone modified by isostearyl acrylate, lauryl acrylate, acryloyl morpholine and unsaturated fatty acid hydroxyalkyl esters. When using such a curing component with a large molecular weight per functional group, an adhesive with a small curing shrinkage can be obtained. As a result, an adhesive layer with a small thickness variation can be obtained. Another example of a curing component is a monomer and / or oligomer having two or more functional groups, such as a (meth) acrylate group or a (meth) acrylamide group. Specific examples thereof include polyethylene glycol diacrylate, trimethylolpropane triacrylate and glycerol triacrylate. As polymerizable compounds other than the above, specifically, for example, tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxane glycol diacrylate, EO-modified diglycerol tetraacrylate, γ-butyrolactone acrylate, hydroxyethyl acrylate, hydroxybutyl acrylate, N-methylpyrrolidone, dimethylacrylamide, hydroxyethyl acrylamide, N-hydroxymethyl acrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, 9-vinyl carbazole, 4-vinylphenyl boronic acid, 3-methacrylamidophenyl boronic acid, fluorenyl acrylate, etc. can be cited. In at least one embodiment of the present invention, the curing component has a ring structure. Specific examples thereof include acryloyl morpholine, γ-butyrolactone acrylate, ε-caprolactone modified by unsaturated fatty acid hydroxyalkyl ester, N-methylpyrrolidone, 9-vinyl carbazole and fluorenyl acrylate. The compound with ring structure has small free volume (high density). Therefore, when using this compound, it is possible to obtain an adhesive with a small curing shrinkage. As a result, it is possible to obtain an adhesive layer with a small thickness variation. Usually two or more curing components can be used in combination. The combination of curing components preferably includes acryloyl morpholine. The preferred combination of curing components includes acryloyl morpholine, tripropylene glycol diacrylate, phenoxy diethylene glycol acrylate and 3-methacrylamide phenyl boronic acid. The active energy ray-curable adhesive may further contain a cationic polymerizable compound as needed. The cationic polymerizable compound may be monofunctional or polyfunctional. Examples of monofunctional cationic polymerizable compounds include p-tert-butylphenyl glycidyl ether, 3-ethyl-3-[(2-ethylhexyl)oxy]oxetane, etc. As a polyfunctional cationic polymerizable compound, for example, 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane can be cited. As a cationic polymerizable compound, a silane coupling agent can be used. An example of a silane coupling agent is 3-glycidoxypropyltrimethoxysilane. The active energy ray curable adhesive may further contain an acrylic oligomer as required. The molecular weight of the acrylic oligomer may be appropriately set according to the purpose. When an acrylic oligomer that does not form any further bonding is used, an adhesive having a small curing shrinkage may be obtained. As a result, an adhesive layer having a small thickness variation may be obtained. Typically, as described above, the active energy ray-curable adhesive contains a photopolymerization initiator. Examples of the photopolymerization initiator include 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, diethylthioxanthone, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 1-hydroxycyclohexylphenyl ketone, and the like. The active energy ray-curable adhesive may further contain a plasticizer (for example, an oligomer component), a crosslinking agent, a diluent, etc., depending on the purpose. Commercially available products may be used for the above components. The thickness of the adhesive layer may be, for example, 0.1 μm to 7.0 μm, for example, 0.5 μm to 6.0 μm, for example, 0.8 μm to 5.0 μm, for example, 1.0 μm to 3.0 μm. The absolute value of the difference between the refractive index of the active energy ray-curable adhesive and the refractive index of the adjacent layer (particularly the first liquid crystal alignment fixing layer) is preferably as small as possible. E. Interlayer bonding layer As described above, the interlayer adhesive layer (not shown) is an adhesive layer for laminating the first liquid crystal alignment fixing layer 21 and the second liquid crystal alignment fixing layer 22. The interlayer adhesive layer may include a pressure-sensitive adhesive, or may include an adhesive. In at least one embodiment of the present invention, the refractive index n of the first liquid crystal alignment fixing layer is LC1 , the refractive index n of the second liquid crystal alignment fixing layer LC2 and the refractive index n of the interlayer adhesive layer AD and the thickness of the interlayer adhesive layer T AD and thickness variation TV AD The formula (1) shown below is satisfied. Unless otherwise specified, the term "refractive index" of the liquid crystal alignment fixing layer as used herein means the refractive index in the transmission axis direction of the polarizer. The adhesive layer is substantially optically isotropic, so the refractive index n AD It is also isotropic. |{(n LC1 +n LC2 ) / 2-n AD}|×(TV AD / T AD )×1,000≤3.0…(1) The left side of formula (1) is preferably 2.5 or less, more preferably 2.0 or less, further preferably 1.8 or less, particularly preferably 1.2 or less, and particularly preferably 0.7 or less. The absolute value of the left side of formula (1) is preferably as small as possible, for example, 0.0. Regardless of whether the interlayer adhesive layer is an adhesive layer or a pressure-sensitive adhesive layer, the refractive index n of the interlayer adhesive layer AD For example, it may be 1.45 or more, or 1.50 or more, or 1.52 or more. The refractive index n of the interlayer adhesive layer is AD It is preferably 1.54 or more, more preferably 1.55 or more, further preferably 1.57 or more, and particularly preferably 1.60 or more. AD It may be, for example, 1.63 or less. When the interlayer adhesive layer is a pressure-sensitive adhesive layer, the thickness T of the interlayer adhesive layer is AD For example, it is 3 μm or more, preferably 4 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, and particularly preferably 15 μm or more. AD For example, it may be 30 μm or less. In the case where the interlayer adhesive layer is an adhesive layer, the thickness T of the interlayer adhesive layer is AD It is preferably 0.5 μm to 2.0 μm, and more preferably 0.8 μm to 1.2 μm. The thickness deviation TV of the interlayer adhesive layer AD It is preferably 0.20 μm or less, more preferably 0.18 μm or less, and further preferably 0.16 μm or less. AD It may be, for example, 0.03 μm or more. For pressure-sensitive adhesive and the adhesive for forming the interlayer adhesive layer, any appropriate configuration can be adopted respectively, as long as the above-mentioned characteristics are met.Regarding pressure-sensitive adhesive, by adjusting the type, quantity, combination and blending ratio of the monomer of the base polymer for forming the pressure-sensitive adhesive, the blending amount of the cross-linking agent, the reaction temperature, the reaction time, etc., a pressure-sensitive adhesive with the desired characteristics corresponding to the purpose can be prepared.As a pressure-sensitive adhesive, for example, the configuration described in Japanese Patent Application Publication No. 2022-008017 can be adopted.Its description is incorporated herein by reference.In addition, regarding adhesive, by adjusting the type, quantity, combination and blending ratio of the curing component, the type, quantity, combination, blending amount, reaction temperature, the reaction time, etc. of the polymerization initiator, the adhesive with the desired characteristics corresponding to the purpose can be prepared.As an adhesive, for example, an adhesive blended with a high refractive index component (typically, inorganic particles) can be used. F. Image display device The optical laminate described in parts A to E can be applied to an image display device. Therefore, an image display device using such an optical laminate is also included in at least one embodiment of the present invention. Typical examples of image display devices include liquid crystal display devices and organic EL display devices. The image display device of at least one embodiment of the present invention typically has the optical laminate described in parts A to E above on the observer side. Example The present invention is specifically described below by way of examples. However, the present invention is not limited to these examples. The measuring methods and evaluation methods in the examples are as follows. Unless otherwise specified, the terms "parts" and "%" in the examples are based on weight. (1) Hardness and elastic modulus The hardness and elastic modulus were measured by nanoindentation under the following measurement conditions using a nanoindenter (manufactured by Hysitron Inc., "Triboindenter"). Specifically, a laminate having a configuration of "polarizer / adhesive layer / first liquid crystal orientation fixing layer" as an intermediate of the optical laminate in each embodiment and comparative example was used as a test sample. The probe (indenter) of the nanoindenter was pressed into the surface of the first liquid crystal orientation fixing layer of the test sample, and the hardness and elastic modulus were calculated from the displacement-load hysteresis curve by the formula shown below. The hardness and elastic modulus thus calculated are defined as the hardness and elastic modulus of the adhesive layer, respectively. Hardness (GPa) = Pmax / A Elastic modulus (GPa) = (√π / 2) × (S / √A) Here, Pmax represents the maximum load obtained from the displacement-load hysteresis curve, A represents the contact projection area between the indenter and the test sample, S represents the slope of the tangent to the unloading curve of the displacement-load hysteresis curve (contact stiffness), and "π" represents the circular ratio. (Measurement conditions) ·Measurement method: Single indentation method Measurement temperature: 25℃ ·Insertion speed: about 2nm / sec Indentation depth: about 300nm Indenter used: Berkovich type (triangular pyramid type) made of diamond (2) Indentation load The test sample was pushed in the same manner as in the above section (1), and the load when the test sample was pushed by 1,000 nm was measured. The measured load was defined as the indentation load of the adhesive layer. (3) Deformation A portion with a size of 850 mm × 160 mm was punched out from a randomly selected area of a stack having a configuration of "polarizer / adhesive layer / first liquid crystal orientation fixing layer" as an intermediate of the optical stack of each embodiment and comparative example, and used as a test sample. The long side direction of the test sample was set to the absorption axis direction of the polarizer. At the same time, a commercially available polarizer (manufactured by Nitto Denko Corporation) and a commercially available delay film (manufactured by FUJIFILM Corporation, product name "QLAB218") were joined to each other so that the absorption axis of the polarizer and the slow axis of the delay film formed an angle of 65°. Thus, an optical film stack was produced. The optical film stack was punched out into a size corresponding to the above-mentioned test sample in such a way that the slow axis became the long side direction, and joined to a glass plate to provide a test stack. The joining was performed in such a way that the polarizer was located on the side of the glass plate. The test sample and the test stack are arranged so that the absorption axis of the polarizer of the test sample and the slow axis of the delay film of the test stack are parallel to each other, and the optical film stack is on the test sample side. Light equivalent to the backlight of the image display device is irradiated from the glass plate side, and the light leakage part (bright spot) is visually observed. The cross section of the bright spot part is observed by a scanning electron microscope (SEM), and the deformation amount of the delay layer (first liquid crystal orientation fixing layer) is calculated from the image. The deformation is in a state where the delay layer protrudes to the opposite side of the adhesive layer. The protrusion amount from the flat portion is defined as the deformation amount, and is evaluated based on the criteria described below. When multiple bright spots are observed, the average value of the deformation amounts at each bright spot is used as the deformation amount. 4 (Satisfactory): No bright spots were observed. 3 (Acceptable): 3 or fewer bright spots were observed and the deformation was less than 60 μm. 2 (moderate): 3 or less bright spots are observed, the deformation amount is 60 μm or more and less than 120 μm, or 4 or more bright spots are observed. 1 (insufficient): A bright spot with a deformation amount of 120 μm or more was observed. [Production Example 1: Preparation of Adhesive A for Forming Adhesive Layer] 20 parts of unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone (manufactured by Daicel Corporation, product name "PLACCEL FA1DDM"), 20 parts of acryloylmorpholine (manufactured by KOHJIN Co., Ltd., product name "ACMO"), 3 parts of diethylacrylamide (manufactured by KJ Chemicals Corporation, product name "DEAA"), 6.7 parts of lauryl acrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Acrylate LA"), 27 parts of isostearyl acrylate (manufactured by Osaka Organic Chemical Industry Ltd., product name "ISTA"), 10 parts of 1,9-nonanediol diacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Acrylate 1,9ND-A"), 13.3 parts of acrylic oligomer (manufactured by Toagosei Co., Ltd., product name "ARUFON UP-1190”), 3 parts of a photopolymerization initiator (2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one) (manufactured by IGM Resins BV, product name “Omnirad 907”), and 3 parts of a photopolymerization accelerator (diethylthioxanthone) (manufactured by Nippon Kayaku Co., Ltd., product name “KAYACURE DETX-S”) were stirred at 50° C. for 1 hour to prepare an adhesive A. [Production Example 2: Preparation of Adhesive B for Forming Adhesive Layer] 40 parts of acryloylmorpholine (manufactured by KOHJIN Co., Ltd., product name "ACMO"), 30 parts of tripropylene glycol diacrylate (manufactured by Toagosei Co., Ltd., product name "ARONIX M-220"), 17 parts of phenoxydiethylene glycol acrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Acrylate P2H-A"), 3 parts of 3-methacrylamidophenylboric acid (manufactured by Junsei Chemical Co., Ltd., product name "MAPBA"), 10 parts of 4-hydroxybutyl acrylate (manufactured by Mitsubishi Chemical Corporation, product name "4HBA"), 3 parts of a photopolymerization initiator (2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one) (manufactured by IGM Resins BV, product name "Omnirad907"), and 3 parts of a photopolymerization accelerator (diethylthioxanthone) (manufactured by Nippon Kayaku Co., Ltd., product name "KAYACURE DETX-S") was stirred at 50°C for 1 hour to prepare Adhesive B. [Production Example 3: Preparation of Adhesive C for Forming Adhesive Layer] 30 parts of acryloylmorpholine (manufactured by KOHJIN Co., Ltd., product name “ACMO”), 30 parts of tripropylene glycol diacrylate (manufactured by Toagosei Co., Ltd., product name “ARONIX M-220”), 27 parts of phenoxydiethylene glycol acrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name “Light Acrylate P2H-A”), 3 parts of 3-methacrylamidophenylboric acid (manufactured by Junsei Chemical Co., Ltd., product name “MAPBA”), 10 parts of 4-hydroxybutyl acrylate (manufactured by Mitsubishi Chemical Corporation, product name “4HBA”), 3 parts of a photopolymerization initiator (2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one) (manufactured by IGM Resins BV, product name “Omnirad907”), and 3 parts of a photopolymerization accelerator (diethylthioxanthone) (manufactured by Nippon Kayaku Co., Ltd., product name "KAYACURE DETX-S") was stirred at 50°C for 1 hour to prepare Adhesive C. [Production Example 4: Preparation of Adhesive D for Forming Adhesive Layer] 10 parts of urethane acrylate oligomer (manufactured by Mitsubishi Chemical Corporation, product name "UV-3000B"), 2.5 parts of tripropylene glycol diacrylate (manufactured by Toagosei Co., Ltd., product name "ARONIXM-220"), 77.5 parts of methyl acrylate (2-methyl-2-ethyl-1,3-dioxolan-4-yl) methyl ester (manufactured by Osaka Organic Chemical Industry Ltd., product name "MEDOL-10"), 10 parts of lauryl acrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Acrylate LA"), and 3 parts of a photopolymerization initiator (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide) (manufactured by IGM Resins BV, product name "Omnirad 819") were stirred at 50°C for 1 hour to prepare Adhesive D. [Example 1] 1. Production of polarizers 1-1. Production of polarizers A polyvinyl alcohol (PVA) film having an average degree of polymerization of 2,400, a degree of saponification of 99.9 mol%, and a thickness of 45 μm is prepared. The PVA film is stretched at a ratio of 2.2 times in the conveying direction, and swelled by immersing it in a swelling bath (water bath) at 30° C. for 30 seconds between rollers having different peripheral speed ratios (swelling step). Subsequently, the film is stretched at a ratio of 3.3 times in the conveying direction based on the original PVA film (PVA film that is completely unstretched in the conveying direction), and dyed by immersing it in a dyeing bath (an iodine aqueous solution obtained by blending iodine and potassium iodide in a weight ratio of 1:7 relative to 100 wt% of water) at 30° C. for 30 seconds, wherein the concentration of iodine is adjusted so that the polarizer to be obtained achieves a predetermined single-layer transmittance (dyeing step). Then, the dyed PVA film is immersed in a cross-linking bath (an aqueous solution of 3.5wt% boric acid concentration, 3.0wt% potassium iodide concentration, and 3.6wt% zinc sulfate concentration) at 40°C for 28 seconds, and stretched at a ratio of 3.6 times relative to the original PVA film in the conveying direction (cross-linking step). In addition, the obtained PVA film is immersed in a stretching bath (an aqueous solution of 4.8wt% boric acid concentration, 5.0wt% potassium iodide concentration, and 5.0wt% zinc sulfate concentration) at 64°C for 60 seconds, and stretched at a ratio of 6.0 times based on the original PVA film in the conveying direction (stretching step). Then, the film is immersed in a washing bath (potassium iodide concentration: 2.3wt%) at 29°C for 10 seconds (washing step). The washed PVA film is dried at 40°C for 30 seconds to produce a polarizer. The resulting polarizer has a thickness of 18μm. 1-2. Production of polarizing film As an adhesive, an aqueous solution containing an acetoacetyl-containing PVA resin (average degree of polymerization: 1,200, saponification degree: 98.5 mol%, acetoacetylation degree: 5 mol%) and methylol melamine in a weight ratio of 3:1 was used. An acrylic resin film (manufactured by Toyo Kohan Co., Ltd., product name "RX-30") was bonded to one surface of the polarizer obtained above via an adhesive, and an HC-TAC film was bonded to the other surface, thereby providing a laminate. The HC-TAC film is a film (thickness: 48 μm) in which a hard coating layer (HC) is formed on a triacetyl cellulose (TAC) film (manufactured by FUJIFILM Corporation, product name "TJ40UL"), and the HC-TAC film is bonded so that the TAC film is on the polarizer side. Bonding is performed using a roll laminator. After joining, the laminate was heated and dried in an oven (temperature 90° C., 10 minutes) to obtain a polarizing plate having a configuration of “HC layer / TAC film (protective layer) / polarizer / acrylic resin film (protective layer)”. 2. Production of delay layer A photopolymerizable liquid crystal compound showing a nematic liquid crystal phase (manufactured by BASF SE, "Paliocolor LC242", the chemical formula is shown below) was dissolved in cyclopentanone to prepare a solution with a solid content concentration of 30 wt%. A surfactant (manufactured by BYK-Chemie GmbH, "BYK-360") and a photopolymerization initiator (manufactured by IGM Resins B.V., "Omnirad 907") were added to the solution to prepare a liquid crystal composition solution. The amount of surfactant and polymerization initiator added was set to 0.01 parts by weight and 3 parts by weight, respectively, relative to 100 parts by weight of the photopolymerizable liquid crystal compound. A biaxially stretched norbornene-based film (manufactured by Zeon Corporation, "ZEONOR film", thickness: 33 μm, Re (550) = 135 nm) was prepared as a substrate. The above liquid crystal composition was applied to the substrate using a rod coater so that Re (550) became 240 nm. The composition was heated at 100°C for 3 minutes to orient the liquid crystal. After the resultant was cooled to room temperature, the product was subjected to a 30-minute exposure to light at a cumulative intensity of 400 mJ / cm 2 The resultant was photocured by irradiation with UV light. Thus, a laminate having a configuration of "substrate / first liquid crystal orientation fixing layer" was obtained. The first liquid crystal orientation fixing layer was uniformly oriented and had a thickness of 1.7 μm. In addition to changing the coating thickness, a laminate having a configuration of "substrate / second liquid crystal orientation fixing layer" (uniform orientation, thickness: 0.92 μm, Re (550) = 130 nm) was obtained in the same manner as above. 3. Production of optical laminates The first liquid crystal orientation fixing layer is bonded to the surface of the acrylic resin film of the polarizer by the adhesive A (thickness: 1.5 μm) of Production Example 1, and then the substrate is peeled off to provide an intermediate stack having a configuration of "polarizer / adhesive layer / first liquid crystal orientation fixing layer". The intermediate stack is evaluated as described in sections (1) to (3) above. The hardness of the adhesive layer is 54.6 (MPa), the elastic modulus is 803 (MPa), and the indentation load is 900 (μN). Next, the second liquid crystal orientation fixing layer is bonded to the surface of the first liquid crystal orientation fixing layer of the intermediate stack by an acrylic pressure-sensitive adhesive (12 μm), and the substrate is peeled off to provide an optical stack having a configuration of "polarizer / adhesive layer / first liquid crystal orientation fixing layer / interlayer adhesive layer / second liquid crystal orientation fixing layer". An acrylic pressure-sensitive adhesive sheet (thickness: 20 μm) is bonded to the surface of the second liquid crystal orientation fixing layer of the resulting optical stack. In the optical laminate, the transmission axis of the polarizer of the polarizing plate and the slow axis of the first liquid crystal alignment fixing layer formed an angle of 15°, and the transmission axis of the polarizer of the polarizing plate and the slow axis of the second liquid crystal alignment fixing layer formed an angle of 75°. [Example 2] An optical laminate was obtained in the same manner as in Example 1, except that the adhesive for forming the adhesive layer was changed to the adhesive B of Production Example 2. The obtained optical laminate was evaluated in the same manner as in Example 1. The results are shown in Table 1. The hardness of the adhesive layer was 71.7 (MPa), the elastic modulus was 1,717 (MPa), and the indentation load was 1,500 (μN). [Example 3] An optical laminate was obtained in the same manner as in Example 1, except that the adhesive used to form the adhesive layer was changed to the adhesive C of Production Example 3. The obtained optical laminate was evaluated in the same manner as in Example 1. The results are shown in Table 1. The hardness of the adhesive layer was 128.0 (MPa), the elastic modulus was 2,172 (MPa), and the indentation load was 2,500 (μN). [Comparative Example 1] An optical laminate was obtained in the same manner as in Example 1, except that the adhesive used to form the adhesive layer was changed to the adhesive D of Production Example 4. The obtained optical laminate was evaluated in the same manner as in Example 1. The results are shown in Table 1. The hardness of the adhesive layer was 22.1 (MPa), the elastic modulus was 123 (MPa), and the indentation load was 250 (μN). Table 1 Example 1 Example 2 Example 3 Comparative Example 1 Adhesive layer Adhesive A Adhesive B Adhesive C Adhesive D Hardness(MPa) 54.6 71.7 128.0 22.1 Elastic modulus (MPa) 803 1,717 2,172 123 Indentation load (μN) 900 1,500 2,500 250 Deformation 3 4 4 1 [evaluate] As is apparent from Table 1, according to the embodiment of the present invention, the first liquid crystal alignment fixing layer is not deformed when it is transferred, and as a result, the yield rate is improved. The optical laminate according to at least one embodiment of the present invention can be suitably used in an image display device (typically a liquid crystal display device or an organic EL display device). According to at least one embodiment of the present invention, an optical laminated body can be realized which includes a liquid crystal alignment fixing layer and suppresses deformation of each liquid crystal alignment fixing layer when it is transferred during production and can be produced with high productivity. Many other modifications will be apparent to those skilled in the art and can be readily practiced without departing from the scope and spirit of the invention.It is therefore to be understood that the scope of the appended claims is not intended to be limited by the details of the specification, but should be broadly interpreted.
Claims
1. An optical laminate, comprising: A polarizing plate including a polarizer; And A retardation layer laminated on the polarizing plate via an adhesive layer, Wherein the retardation layer sequentially includes from the polarizing plate side: A first liquid crystal alignment fixing layer, and A second liquid crystal alignment fixing layer, Wherein the retardation layer as a whole has either a circular polarization function or an elliptical polarization function, and has the relationship of Re(450) < Re(550) < Re(650), and Wherein the adhesive layer has a hardness of 50 MPa or greater, an elastic modulus of 800 MPa or greater, and an indentation load of 900 μN or greater.
2. The optical laminate according to claim 1, wherein the adhesive layer contains a radiation curable adhesive.
3. The optical laminate according to claim 2, wherein the radiation curable adhesive contains acrylmorpholine as a curing component.
4. The optical laminate according to claim 3, wherein the radiation curable adhesive further contains dipropylene glycol diacrylate, phenoxy diethylene glycol acrylate, and 3-methacrylamidophenylboronic acid as curing components.
5. The optical laminate according to claim 4, wherein the adhesive layer has a hardness of 70 MPa or greater, an elastic modulus of 1,500 MPa or greater, and an indentation load of 1,300 μN or greater.
6. The optical laminate according to any one of claims 1 to 5, wherein the first liquid crystal alignment fixing layer has a thickness of 1.7 μm or less.
7. An image display device, comprising the optical laminate according to any one of claims 1 to 5.
Citation Information
Patent Citations
Liq. crystalline (LC) material
DE19504224A1
Novel polymerizable liquid crystalline compounds
DE4408171A1
Liquid crystalline reticulated polysiloxanes
EP0066137A1
Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer
EP0261712A1
Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups
EP0358208A2